2000
DOI: 10.1002/chin.200045255
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Mesoporous Zeolite Single Crystals.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…detail in section 3.1. Other solid templates include resins, 44 organic aerogels, 45,46 and polymers, 47,48 biological templates such as bacteria, 49 plants, 50,51 and starch, 52 as well as purely inorganic compounds such as Mg(OH) 2 53 and CaCO 3 . 53,54 The supramolecular templating method involves the use of surfactant molecules to actively direct the synthesis of large micropores or mesopores.…”
Section: Templating Methodsmentioning
confidence: 99%
“…detail in section 3.1. Other solid templates include resins, 44 organic aerogels, 45,46 and polymers, 47,48 biological templates such as bacteria, 49 plants, 50,51 and starch, 52 as well as purely inorganic compounds such as Mg(OH) 2 53 and CaCO 3 . 53,54 The supramolecular templating method involves the use of surfactant molecules to actively direct the synthesis of large micropores or mesopores.…”
Section: Templating Methodsmentioning
confidence: 99%
“…131 Although nanosized zeolite crystal synthesis requires an incipient wetness impregnation of the material with an amount of zeolite synthesis gel lower than the total volume of the porosity to restrict the crystallization to the pore system, Jacobsen et al 20. 133, 135 reported that the use of a light excess of synthesis gel, with a sufficient concentration, led to the growth of large zeolite crystals that engulfed carbon black particles. It is essential that the nucleation of the zeolite takes place exclusively between the particles, which will not occur by simply dip‐coating into the synthesis gel.…”
Section: Constructive Synthesis Strategiesmentioning
confidence: 99%
“…By removal of the carbon matrix by controlled calcination, so‐called mesoporous zeolite single crystals (Figure 8), were obtained and exhibited a bimodal pore distribution, owing to the additional intracrystalline mesopore system with a broad pore size distribution in the range of 10–100 nm interconnected to the zeolite micropores. Since this discovery, this versatile method has been employed with a wide range of solid templates, such as carbon black,20, 133, 135138 single‐ or multi‐walled carbon nanotubes,135, 139–141 carbon nanofibers,142, 143 carbon or polymer aerogel,144146 ordered mesoporous carbon (CMK types),147, 148 non‐ordered mesoporous carbon,149 wood cells,150 and silica‐containing plants such as Equisetum arvense ,151, 152 or rattan stems 153. Recent reviews give a good overview of these methods 70.…”
Section: Constructive Synthesis Strategiesmentioning
confidence: 99%
“…Recently, Tsapatsis and co-workers have successfully imprinted ordered mesoporous zeolite crystals by three-dimensionally ordered mesoporous (3DOM) carbons with pore size of 10-40 nm [102]. Of course, the solid template is not limited to carbon, and many solid materials such as CaCO 3 and MgO as well as biomaterials have been used to template mesoporous zeolites [108][109][110]. Notably, industrial applications of mesoporous zeolites templated from solid carbons are still limited because of the complexity of synthetic procedures and the hydrophobicity of the carbon templates.…”
Section: Templating Routesmentioning
confidence: 98%